PENGARUH LATIHAN SKIPPING TERHADAP KECEPATAN TENDANGAN SABIT PENCAK SILAT SMA NEGERI KEBERBAKATAN OLAHRAGA BAHTERAMAS SULAWESI TENGGARA - Sariana; Asnan, Wahyu; Nurfuadi, Diki; Muhammad Feril Anugrah; Istiqomah, Fainsyah (Jurnal Pedagogik Olahraga, 2025)
The purpose of this study was to determine the effect of skipping training on the speed of pencak silat sickle kicks in students at State High School for Sports Talent. This research used an experimental method, the population in the research was all 190 State High School students with Sports Talent. The sampling technique used a purposive sampling technique, this technique was carried out based on considerations with certain criteria so that a research sample of 19 people was obtained. The test instrument used was a pencak silat sickle kick speed test, then skipping training was given with a training volume of 3 times for 18 meetings. The research data was analyzed using the t statistical test using SPSS version 25. Based on the analysis results, the pretest average was 14.21 and the posttest average was 18.32, this shows that the training carried out was able to bring about changes in the speed of the sickle kick compared to before the training was given. The results obtained from hypothesis testing show a significant value of 0.000 < 0.05, so Ho is rejected and Ha is accepted, which means that there is a significant influence of skipping training on the speed of sickle kicks at the Bahteramas Sports Gifted High School, Southeast Sulawesi.